The Nonstate Provision of Health Services and Citizen Accountability in Uganda - Katusiimeh, Mesharch W. (Indiana University Press, 2015)
Uganda is one of the many countries in the Global South where nonstate actors’ involvement in delivering social services has grown in numbers, diversity, and importance. Indeed, nonstate provision plays a major role in the delivery of health services. As a result, nonstate providers (NSPs) have increasingly been recognized by governments and donors to be instrumental in helping realize the health-related Millennium Development Goals (MDGs). Existing studies on the nonstate provision of social welfare have focused on technical and administrative concerns, particularly in developing countries, such as the relative efficiency of the public versus the private provision of social services (Katusiimeh 2012; Ndandiko 2010). However, recent literature has concluded that nonstate provision can have profound effects on political life, particularly on equity (access to social welfare), state capacity, and accountability (Brass 2014; Cammett and MacLean 2011, 2014). To date, little empirical research explores the political consequences of the nonstate provision of social welfare, particularly in the context of sub-Saharan Africa.
Keywords: Nonstate Provision; Health Services; Citizen Accountability